Applying six sigma-process capability in predicting users satisfaction for excellence library service decision making - Taib, Che Azlan (2016)
Six Sigma (6s) refers to a set of tools and methodologies developed to focus on reducing process variation and improve process capability . The main concept or cornerstone of 6s is the normal probability distribution, and sigma represents the standard deviation, which is a measure of the variability within a population around a mean.This paper attempts to enhance understanding of the application of 6s process capability in measuring library services.In addition, it tries to predict the process variation , productivity and process capability for academic library services.It is also significant for library staff to know the distribution of library users' satisfaction level and how they would be able to assist them in improving their library service.The study was conducted at Sultanah Bahiyah Library (SBL), Universiti Utara Malaysia (UUM).The result of the study show both Cpk and Cp are 0.56. Since the value of Cpk and Cp are less than 1.00, the SBL is not capable to meet users' requirements. The conclusion can also be drawn that the collective results of these studies present the unique contributions of 6s process capability and play a significant role in measuring and predicting library services.Following detail analysis of preliminary study results, implications of this paper and suggestions for future research in the efforts to document the impact of 6s in library services are also presented.